2009
DOI: 10.1039/b821882j
|View full text |Cite
|
Sign up to set email alerts
|

Solid phase synthesis and structural analysis of novel A-chain dicarba analogs of human relaxin-3 (INSL7) that exhibit full biological activity

Abstract: Replacement of disulfide bonds with non-reducible isosteres can be a useful means of increasing the in vivo stability of a protein. We describe the replacement of the A-chain intramolecular disulfide bond of human relaxin-3 (H3 relaxin, INSL7), an insulin-like peptide that has potential applications in the treatment of stress and obesity, with the physiologically stable dicarba bond. Solid phase peptide synthesis was used to prepare an A-chain analogue in which the two cysteine residues that form the intramole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 29 publications
0
44
0
2
Order By: Relevance
“…Competition binding experiments were performed with either europium-labeled H2 relaxin (26) or Eu 3ϩ -labeled INSL3 (27) in the absence or presence of increasing concentrations of unlabeled hormones. Nonspecific binding was determined with an excess of unlabeled peptides (500 nM H2 relaxin or INSL3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Competition binding experiments were performed with either europium-labeled H2 relaxin (26) or Eu 3ϩ -labeled INSL3 (27) in the absence or presence of increasing concentrations of unlabeled hormones. Nonspecific binding was determined with an excess of unlabeled peptides (500 nM H2 relaxin or INSL3).…”
Section: Methodsmentioning
confidence: 99%
“…All H2 relaxin analogues synthesized in this study contain two chains and three disulfide bonds. Both regioselectively S-protected A-and B-chains were synthesized separately by the continuous flow Fmoc solidphase method (24) using an automatic PerSeptive Biosystems Pioneer peptide synthesizer (Framingham, MA) or by using microwave-assisted synthesis on a Liberty system (CEM Corp.) (21,23,25,26).…”
Section: Methodsmentioning
confidence: 99%
“…The residues in the B-chain central a-helix that are involved in RXFP3 binding have also been identified, and it was shown that activation is mediated via two critical C-terminal residues, ArgB26 and TrpB27 [47]. Replacement of the intra-A-chain disulfide bond with a dicarba bond did not cause loss of biological activity and also increased in vitro serum stability [48]. Furthermore, replacement of the A-chain with that from INSL5 (R3/I5) confers selectivity to RXFP3 and RXFP4 by substantially reducing affinity for the relaxin receptor, RXFP1 [47,49].…”
Section: Structure-function Relationship Studiesmentioning
confidence: 96%
“…A significant advance in the solid phase synthesis of INSLs was heralded by the successful synthesis of H2 relaxin via regioselective disulfide bond formation, in which each of the three disulfide bonds were formed sequentially by stepwise removal of pairs of orthogonal S-protecting groups followed by oxidation of the resulting liberated thiol groups [17]. A complex eight-step strategy was followed in which the A-chain was assembled by Fmoc chemistry SPPS and contained three different S-protecting groups, each removable by a different chemical 48 …”
Section: Synthesis Of Relaxinmentioning
confidence: 99%
“…Cyclotides, disulfide rich cyclic peptides, have been isolated for the first time from the Melicytus family of plants (Trabi et al, 2009). Using solid phase chemistry, a novel A-chain analogue of human relaxin-3 (INSL7) has been synthesised in which the intramolecular disulfide bond is replaced with a non-reducable carbon-carbon bond (Hossain et al, 2009). A novel class of peptidomimetics, Ψ[CH(CF 3 )NH]Gly peptides, have been reported, which utilises a stereogenic trifluoroethylamine group as a peptide bond mimic (Molteni et al, 2009).…”
Section: The Chemical Biology Of Proteinsmentioning
confidence: 99%